Association of the polymorphisms of the cholesteryl ester transfer protein gene with coronary artery disease: a meta-analysis - Zhang, Ruizhe; Xie, Qingya; Xiao, Pingxi (Frontiers in Cardiovascular Medicine, 2023)
Aims: This meta-analysis aimed to assess the association of the polymorphisms of cholesterol ester transfer protein (CETP) rs708272 (G>A), rs5882 (G>A), rs1800775 (C>A), rs4783961 (G>A), rs247616 (C>T), rs5883 (C>T), rs1800776 (C>A), and rs1532624 (C>A) with coronary artery disease (CAD) and the related underlying mechanisms. Methods: A comprehensive search was performed using five databases such as PubMed, EM-BASE, Web of Science, Cochrane Library and Scopus to obtain the appropriate articles. The quality of the included studies was assessed by the Newcastle-Ottawa Scale. The statistical analysis of the data was performed using STATA 17.0 software. The association between CETP gene polymorphisms and risk of CAD was estimated using the pooled odds ratio (OR) and 95% confidence interval (95% CI). The association of CETP gene polymorphisms with lipids and with CETP levels was assessed using the pooled standardized mean difference and corresponding 95% CI. P < 0.05 was considered statistically significant. Results: A total of 70 case-control studies with 30619 cases and 31836 controls from 46 articles were included. The results showed the CETP rs708272 polymorphism was significantly associated with a reduced risk of CAD under the allele model (OR = 0.846, P < 0.001), the dominant model (OR = 0.838, P < 0.001) and the recessive model (OR = 0.758, P < 0.001). AA genotype and GA genotype corresponded to higher high-density lipoprotein cholesterol (HDL-C) concentrations in the blood compared with GG genotype across the studied groups (all P < 0.05). The CETP rs5882 and rs1800775 polymorphisms were not significantly associated with CAD under the allele model (P = 0.802, P = 0.392), the dominant model (P = 0.556, P = 0.183) and the recessive model (P = 0.429, P = 0.551). Similarly, the other mentioned gene polymorphisms were not significantly associated with CAD under the three genetic models.The CETP rs708272 polymorphism shows a significant association with CAD, and the carriers of the allele A are associated with a lower risk of CAD and higher HDL-C concentrations in the blood compared to the non-carriers. The CETP rs5882, rs1800775, rs4783961, rs247616, rs5883, rs1800776, and rs1532624 are not significantly associated with CAD.